De l’ordre moral à l’ordre social. L’application des lois pénalisant la sexualité prémaritale selon des lignes de classe - Mériam Cheikh (L’Année du Maghreb)
The analysis of sex-work practices in terms of intimate economy in Morocco allows, on the one hand, to link generally separated sexual practices (acts of prostitution and intimate sexual acts not prostitution) and, on the other hand, to observe how these practices are addressed by the police in a country where sexuality outside marriage remains illegal. Therefore, this article seeks to illustrate and analyse an observation of the evolution of the criminalization of morals and the work of the police squads through ethnographic data and a review of the local press (Tangier) playing an important role in the evolution of the police relation to “moral crimes”. The legal prohibition of sexual relations outside marriage has largely become a dead letter due to the fact that the public authorities take into account in their everyday work the evolution of mores. However, the analysis of policies regulating morals and police work shows how the criminalisation tends to be implemented only against girls of varying profiles but all in a precarious situation – apart from the cases that are exploited for political purposes – which the police bring in, without embarrassing themselves of the harm done to those who do not practice “the going out”, in the homogeneous category of “prostitutes”. This modality of police action reinforces a de facto distinction between good and bad femininities that no longer correspond to the local moral opposition between virgins and non-virgins, or between “house girls” and “street girls”. The opposition is thus between legitimate and illegitimate practices of out of wedlock intimacy and night-time entertainment. Since the legitimacy and illegitimacy of these practices are largely correlated with the social status of the girls concerned and their positions within the social space of the intimate economy that they occupy at some point in their trajectory, the differentiated treatment of sexual illegality apparent therefore to the maintenance of a social order under the guise of preserving the moral order.